Permafrost Thaw and Liberation of Inorganic Nitrogen in Eastern Siberia. (25th September 2017) - Beermann, Fabian; Langer, Moritz; Wetterich, Sebastian; Strauss, Jens; Boike, Julia; Fiencke, Claudia; Schirrmeister, Lutz; Pfeiffer, Eva‐Maria; Kutzbach, Lars
Abstract: The currently observed climate warming will lead to widespread degradation of near‐surface permafrost, which may release substantial amounts of inorganic nitrogen (N) into arctic ecosystems. We studied 11 soil profiles at three different sites in arctic eastern Siberia to assess the amount of inorganic N stored in arctic permafrost soils. We modelled the potential thickening of the active layer for these sites using the CryoGrid2 permafrost model and representative concentration pathways (RCPs) 4.5 (a stabilisation scenario) and 8.5 (a business as usual emission scenario, with increasing carbon emissions). The modelled increases in active‐layer thickness (ALT) were used to estimate potential annual liberation of inorganic N from permafrost soils during the course of climate change. We observed significant stores of inorganic ammonium in permafrost, up to 40‐fold higher than in the active layer. The modelled increase in ALT under the RCP8.5 scenario can result in substantial liberation of N, reaching values up to the order of magnitude of annual fixation of atmospheric N in arctic soils. However, the thaw‐induced liberation of N represents only a small flux in comparison with the overall ecosystem N cycling. Copyright © 2017 John Wiley & Sons, Ltd.